POLITIK HUKUM OMNIBUS LAW DALAM KONTEKS PEMBANGUNAN EKONOMI INDONESIA - Agus Darmawan (Indonesian Journal of Law and Policy Studies, 2020)
The research aims to formulate the politics of the omnibus law law as an effort by the Government to increase investment to advance the economy and prosperity of all Indon people. This study uses a normative approach. The results showed that the omnibus law had not been formulated effectively and accountably so that it needed improvement. The formulation and implementation of the Omnibus Law, it must be balanced at the level of effectiveness and accountability by paying attention to the juridical, political, sociological and economic aspects. Advocacy from all elements of the nation at the level of formulation and implementation of the omnibus law will effectively realize increased investment in economic development for the welfare of all the people of Indonesia.